The assessment of functional communication in patients with acquired communication problems: the development of the Derby Functional Communication Scale - Ditchfield, Jennifer A. (2008)
The Derby Functional Communication Scale (DFCS) was developed to assess functional communication in patients in hospital and rehabilitation settings. The validity of the DFCS and its sensitivity to low mood was also examined. In this study, correlation analysis was undertaken between DFCS and other existing measures of communication and mood. Assessments took place on local Stroke and Rehabilitation units. Sixteen hospital inpatients with acquired communication problems due to mixed aetiologies were assessed on the DFCS and other measures of communication and mood. Measures used included the DFCS, Frenchay Aphasia Screening Test (FAST), Edinburgh Functional Communication Profile (EFCP), Speech Questionnaire (SQ) and speech and language therapists (SaLT) ratings of global communication ability were used to assess communication. The Visual Analogue Mood Scales (VAMS) and the Stroke Aphasic Depression Questionnaire (SADQ) were administered as measures of low mood. The data indicated that DFCS scores were significantly related to other measures of communication (r = .75-.9, p<.01). Inter-rater reliability was generally good for the DFCS with the exception of the 'understanding' subscale, where a low correlation between staff and SaLT ratings was found. No significant (p>0.05) correlations between DFCS and measures of mood were found. In conclusion, the DFCS may be used for assessing observable communication skills in patients with acquired communication disorders. However, further validation and evaluation of the sensitivity to low mood is required.